Born in Britain: a reflection on government aspirations a decade on - D. H. Backaby; P. D. Murphy; N. C. O'Leary (Economics & Finance Research, 2013)
In light of substantial disadvantage faced by ethnic minorities, the UK government stated a decade ago that in 10 years' time, ethnic minorities should no longer face disproportionate barriers to labour market achievement. From the investigation of the stock of native born ethnics conducted here, it is evident that such aspirations have not been realized.
Keywords: 330